The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s1517-83822009000200028
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of extracellular lipase from a new strain: Pseudomonas aeruginosa SRT 9

Abstract: An extra cellular lipase was isolated and purified from the culture broth of Pseudomonas aeruginosa SRT 9 to apparent homogeneity using ammonium sulfate precipitation followed by chromatographic techniques on phenyl Sepharose CL-4B and Mono Q HR 5/5 column, resulting in a purification factor of 98 fold with specific activity of 12307.8 U/mg. The molecular weight of the purified lipase was estimated by SDS-PAGE to be 29 kDa with isoelectric point of 4.5. Maximum lipase activity was observed in a wide range of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 39 publications
2
33
1
2
Order By: Relevance
“…similar to the observed activity increase of FS02 in the current work, enzymatic activity of an alkaline lipase was shown to be increased in the presence of e.g. methanol [31], and high solvent tolerance of a Pseudomonas lipase has been shown [30]. Hence enzyme activity increase in the presence of solvents observed for FS02 is not unique; however, despite of some uncertainties concerning the absolute activity levels from high standard deviations in the analyses, the increases in activity observed for enzymes in previous studies are rarely as high as observed for FS02, rendering the newly discovered enzyme with distinct features compared to other similar enzymes.…”
Section: Production Of Fs02 Enzyme and Enzyme Characterizationsupporting
confidence: 88%
See 1 more Smart Citation
“…similar to the observed activity increase of FS02 in the current work, enzymatic activity of an alkaline lipase was shown to be increased in the presence of e.g. methanol [31], and high solvent tolerance of a Pseudomonas lipase has been shown [30]. Hence enzyme activity increase in the presence of solvents observed for FS02 is not unique; however, despite of some uncertainties concerning the absolute activity levels from high standard deviations in the analyses, the increases in activity observed for enzymes in previous studies are rarely as high as observed for FS02, rendering the newly discovered enzyme with distinct features compared to other similar enzymes.…”
Section: Production Of Fs02 Enzyme and Enzyme Characterizationsupporting
confidence: 88%
“…Lipase activity in the presence of different solvents has been analyzed in several previous studies, mainly showing no or negative effects; e.g. unaffected activity with methanol, ethanol and acetone, and a decreased lipase activity in the presence of isopropanol [30], or reduced lipase activity in the presence of isopropanol, methanol, acetone, acetonitrile and/or ethanol [27] [29]. On the other hand, Figure 2.…”
Section: Production Of Fs02 Enzyme and Enzyme Characterizationmentioning
confidence: 99%
“…Reported reaction times varied from 8 hours for immobilized enzymes to 90 hours for the same free enzymes, depending on the feedstock and alcohol [25]. Moreover, temperature of 55°C as the working temperature for lipases from P. aeruginosa has been reported [28,29]. This temperature showed, for all the cases, the best balance between stability and reaction rate.…”
Section: Discussionmentioning
confidence: 98%
“…We carried out a partial purification process that must be improved further according the results. Other researches had reached lipase purification factors of approximately 300, improving their activity approximately 1000-fold compared to the enzyme supernatant [15,28,47]. Also, protein engineering is widely used to improve the lipase production yields and enzymatic activity [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…3c). Lipase activity of Pseudomonas aeruginosa MTCC 2488 was drastically reduced in the presence of 2-propanol, hexane and butanol (Borkar et al 2009). Also, the lipase activity of Pseudomonas aeruginosa SRT 9 was drastically reduced in the presence of ethanol, butanol and isopropanol (Chouhan and Dawande 2010).…”
Section: Effect Of Organic Solvents On Lipase Activitymentioning
confidence: 97%